12a-(-9)=23

Simple and best practice solution for 12a-(-9)=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12a-(-9)=23 equation:


Simplifying
12a + -1(-9) = 23

Multiply -1 * -9
12a + 9 = 23

Reorder the terms:
9 + 12a = 23

Solving
9 + 12a = 23

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 12a = 23 + -9

Combine like terms: 9 + -9 = 0
0 + 12a = 23 + -9
12a = 23 + -9

Combine like terms: 23 + -9 = 14
12a = 14

Divide each side by '12'.
a = 1.166666667

Simplifying
a = 1.166666667

See similar equations:

| 44=2w^2-3w | | x-7x-3x-8x= | | 2x^2-5xy-3-y^2=0 | | a-24=16 | | 12f^3+30f^2+14f+35=0 | | 0.33x+6=21 | | 135=-5x-5(2x-3) | | 0=-2x-5(-x+3) | | .4(x-5)=3x+1 | | 4t^2-6t-4=0 | | -24m^2n-6mn= | | 12-10[6-2(-4)]=0 | | 4q^2+18q+20=0 | | -31+(-28)-(14)-18= | | 0=-2x-5(-x+15) | | 2q^2-44q-46=0 | | 7f^2+84f+77=0 | | 5x+32=65 | | (3-4i)(5-6i)= | | 5x^2+0x-125=0 | | 4x^3+5x^2-9x-18=0 | | -0.10(10)+0.25x=0.05(x-12) | | x+2i=4-yi | | 2i+i^2= | | x-15x+36= | | 4w=-5w-36 | | 25m^2+35m+10=0 | | -7t=-5t+2 | | 24x-3=-16x+27 | | 113-(5x+6)=5(x+6)+x | | 2w+12=7w-3 | | 2(2m-5)=4m+7 |

Equations solver categories